The complicated lives of Nigerian immigrants in South Africa - Adeoye, Emmanuel Aanu (My University, 2021)
This thesis investigates the motivation of Nigerian migration to South Africa. The thesis explores the diverse experiences of Nigerian immigrants and what role class plays. And it explains why some refuse to return to Nigeria despite the obstacles they face. It investigates the causes of xenophobia and explains the stereotypes that have earned Nigerians an unfair reputation. South Africa’s first democratic elections in 1994 was a moment of optimism. Nigeria was experiencing economic and political turmoil at the time. The lure of economic opportunities has led some 30,000 Nigerians to South Africa. Some are middle class or higher, working as doctors and academics. Some are undocumented migrants navigating a complex situation, sometimes on the receiving end of xenophobic violence. Shops have been looted or razed; some have died. This thesis is divided into two parts: a longform article titled “The complicated lives of Nigerian immigrants in South Africa” based on information garnered through interviews with subjects some of whom are identified with pseudonyms, academic research and media reports. The article contains some elements of my own experience as a Nigerian student in South Africa. The second part is the academic method document that underpins the project
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts (in Journalism and Media Studies), Faculty of Humanities, University of the Witwatersrand, 2021